Grain Boundary and Surface Segregation in Relation to Intergranular Fracture at High Temperature: Boron and Sulfur in a Fe-Cr-Ni Alloy. (2015) - Chen, T.; Chen, X.D.; Lian, X.M.; Liu, C.J.
Abstract: Microstructural features of Fe-Cr-Ni alloy with boron addition have been investigated by field emission gun scanning electron microscopy (FEG-SEM) equipped with an Oxford INCA energy dispersive X-ray spectrometer (EDS). Stress rupture tests were conducted at 1100 ̊C and 17 MPa in air. The results show that sulfur segregates strongly to free surfaces and much less strongly to grain boundaries. (Cr, Mn)S grows along the NbC particles. Boron segregates strongly to grain boundaries (GB) than to free surface. Boron segregation has been observed along GBs between M23 C6 and NbC, between NbC and (Cr, Mn)S. The strengthening mechanism of boron element on creep of the Fe-Cr-Ni alloy was also proposed. Boron segregated to the GB, such as the GB between NbC and (Cr, Mn)S resulting in delaying the selective segregation of sulfur the free surface.